SUIT: The simple user interface toolkit - Pausch, Randy; DeLIne, Robert; Conway, Matthew (CHI '92 Posters and Short Talks of the 1992 SIGCHI Conference on Human Factors in Computing Systems, 1992)
User interface support software, such as UI toolkits, UIMSs, and interface builders, are currently too complex for undergraduates. Tools typically require a learning period of several weeks, which is impractical in a semester course. Most tools are also limited to a specific platform, usually either Macintosh, DOS, or UNIX/X. This is problematic for students who switch from DOS or Macintosh machines to UNIX machines as they move through the curriculum. The situation is similar to programming languages before the introduction of Pascal, which provided an easily ported, easily learned language for undergraduate instruction.